2022
DOI: 10.1111/pce.14504
|View full text |Cite
|
Sign up to set email alerts
|

Integration of reactive oxygen species and nutrient signalling to shape root system architecture

Abstract: Yield losses due to nutrient deficiency are estimated as the primary cause of the yield gap worldwide. Understanding how plant roots perceive external nutrient status and elaborate morphological adaptations in response to it is necessary to develop reliable strategies to increase crop yield. In the last decade, reactive oxygen species (ROS) were shown to be key players of the mechanisms underlying root responses to nutrient limitation. ROS contribute in multiple ways to shape the root system in response to nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 113 publications
(185 reference statements)
0
7
0
Order By: Relevance
“…In general, levels of ROS produced in this experiment did not hinder the growth of duckweeds, either in response to bacteria or IAA. Any detrimental effect of interactions with bacteria is outweighed by potential benefits, e.g., more efficient nutrient uptake [49]. This might be an additional explanation for the biomass increase in duckweeds inoculated with P. gessardii C31-106.…”
Section: Effects Of Pseudomonas Strains and Iaa On The Mda And H 2 O ...mentioning
confidence: 99%
“…In general, levels of ROS produced in this experiment did not hinder the growth of duckweeds, either in response to bacteria or IAA. Any detrimental effect of interactions with bacteria is outweighed by potential benefits, e.g., more efficient nutrient uptake [49]. This might be an additional explanation for the biomass increase in duckweeds inoculated with P. gessardii C31-106.…”
Section: Effects Of Pseudomonas Strains and Iaa On The Mda And H 2 O ...mentioning
confidence: 99%
“…We measured the total ROS content and found that it was about 252.40 ng/mL in B73 and about 147.70 ng/mL in zmnac17-1; i.e., the content of ROS was significantly higher (by 41%) in the mutant (Figure 5A). The content of ROS in plants is closely related to glutathione (GSH), oxidized glutathione (GSSG), catalase (CAT), POD, and SOD, among other factors [14]; therefore, we tested the activity of these enzymes. The results showed that GSH was present at 0.65 umol/g in B73 and 0.75 umol/g in zmnac17-1; i.e., the content of GSH was 15% higher in zmnac17-1.…”
Section: Ros Level Change In Zmnac17-1 Mutant During Mesocotyl Elonga...mentioning
confidence: 99%
“…ROS production and processing are linked to NADPH oxidase, superoxide dismutase (SOD), class III peroxidase (POD), etc. [14], where POD participates in the formation of maize lignin, which is related to cell wall hardening and mesocotyl elongation [15]. Additionally, ROS affect auxin metabolism, distribution, transport, and signal transduction [16].…”
Section: Introductionmentioning
confidence: 99%
“…The latter mainly focused on aspects of source versus sink strength under stress (Murchie et al., 2023; Yu et al., 2015), photosynthetic parameters (Furbank et al., 2015; Nowicka et al., 2018), or photorespiratory losses (Engqvist & Maurino, 2017; Jin et al., 2022; South et al., 2019). Others set out to modulate cell‐wall fortification (Wang et al., 2016), flowering time (Ionescu et al., 2017), stress signalling (Joshi et al., 2018; Tarkowski et al., 2022), or devised climate‐smart combinations thereof (Jansson et al., 2018). In part, these approaches took advantage of mutants and gene stacking (Kudo et al., 2019), and/or the combination of crop lines that are resilient to multiple stresses (Rivero et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increased flux through the irreversible OPPP reactions does not only support oxidative bursts at the plasma membrane, followed by redox signalling and recovery, but may also promote the biosynthesis of specific compounds needed for stress adaptation and/or development: for example, proline with protective roles under both abiotic (Giberti et al., 2014; Sabbioni et al., 2021) and biotic stress conditions (Okumoto et al., 2016; reviewed in Alvarez et al., 2022). Of note, ROS signalling also shapes plant architecture in response to nutritional cues (Tarkowski et al., 2022).…”
Section: Introductionmentioning
confidence: 99%